2012
DOI: 10.22201/ie.20074484e.2012.2.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Temporal niche overlap of a riparian forest bat assemblage in subtropical Mexico

Abstract: Use of time as mediator of ecological interactions is important but has been poorly studied and has received less attention than other niche axes. We characterized and compared patterns of activity, and temporal activity overlap of a bat assemblage at a riparian forest from La Peregrina Canyon, Tamaulipas, Mexico. Bats were captured during twenty one-nights, distributed over a year, using mistnets. Nets were opened before sunset and closed 13 h later, being checked every 30 min. A total of 22 species were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Several Neotropical frugivorous bat assemblages (Phyllostomidae) have been analysed with these methods, with most assemblages evincing more overlap in their activities than at random (Arriaga-Flores et al . 2012, Castro-Arellano et al . 2009, Presley et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several Neotropical frugivorous bat assemblages (Phyllostomidae) have been analysed with these methods, with most assemblages evincing more overlap in their activities than at random (Arriaga-Flores et al . 2012, Castro-Arellano et al . 2009, Presley et al .…”
Section: Introductionmentioning
confidence: 99%
“…High species richness in RS sites was also accompanied by considerable variation in species’ capture rates with few very abundant species, several common species and many captured only a few times. This pattern is typical for phyllostomid bat species in Neotropical areas (Arriaga‐Flores et al, ; Estrada, Coates‐Estrada, Meritt, Montiel, & Curiel, ). The number of species captured rarely may reflect their use of riparian strips as movement corridors among larger forest patches, rather than permanent occupancy in riparian strips.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies found riparian vegetation is crucial to ensure bat mobility across human-modified landscapes (Galindo-Gonzalez & Sosa, 2003). Other studies also observed higher richness of phyllostomid species in riparian forest when compared to open areas or continuous mature forest (Arriaga-Flores et al, 2012;de la Pena-Cuellar et al, 2015;Lourenco et al, 2014). This may also indicate that riparian forest strips add value when compared to forest corridors without streams.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations